2020
DOI: 10.1038/s41598-020-61803-8
|View full text |Cite
|
Sign up to set email alerts
|

Improved viability and fertility of frozen-thawed dog sperm using adipose-derived mesenchymal stem cells

Abstract: Cryopreservation procedures negatively affect the quality traits of sperm, causing certain changes at structural and molecular levels due to thermal, mechanical, osmotic, and oxidative damage. The objective of this study was to examine the potential of canine adipose-derived mesenchymal stem cells (Ad-MSCs) for providing protection to the dog sperm against cryo-damage. Canine Ad-MSCs were selected on the basis of the significantly higher gene expression for different proteins actively involved in the cell repa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…In addition, fibronectin, an ECM component that acts as a growth factor [ 99 ], was found in the cAMSC-CM, which is also involved in protecting membrane integrity ( Table S2 and Table 1 ). Qamar et al [ 100 ] showed that fibronectin was expressed in adipose-derived MSCs and that plasma membrane integrity was protected when adipose-derived MSCs were added to the freezing media. This suggests that cAMSC-CM protected plasma membrane integrity in the present study ( Table 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, fibronectin, an ECM component that acts as a growth factor [ 99 ], was found in the cAMSC-CM, which is also involved in protecting membrane integrity ( Table S2 and Table 1 ). Qamar et al [ 100 ] showed that fibronectin was expressed in adipose-derived MSCs and that plasma membrane integrity was protected when adipose-derived MSCs were added to the freezing media. This suggests that cAMSC-CM protected plasma membrane integrity in the present study ( Table 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…The sperm cryopreservation process involves freezing and thawing, leading to significant physiological and chemical changes in the sperm, which in turn causes the production of reactive oxygen species (ROS) [ 40 , 44 ]. This is mainly due to the removal of seminal plasma during the cryopreservation process, which reduces antioxidant defenses in sperm; thus, sperm become vulnerable to oxidative stress [ 31 ].…”
mentioning
confidence: 99%
“…Methods used for analyzing sperm plasma membrane are normally based on the enhanced permeability of damaged membrane [ 107 ]. These methods include the hypo-osmotic swelling (HOS) test [ 108 , 109 ], eosin–nigrosin staining [ 110 , 111 ], and use of fluorescent probes [ 112 , 113 ]. Fluorescent probes such as Hoechst or propidium-iodide (PI) are either used alone or in combination with other permeable fluorochromes such as carboxyfluorescein diacetate or SYBR [ 114 116 ].…”
Section: Plasma Membrane Integritymentioning
confidence: 99%